The Analysis Study of Comparison of Effectiveness and Safety of Inhalers in Mild-to Moderate Asthma in Adults: A Comprehensive Systematic Review - Harve, Akbar Fathoni (International Medical Journal Corp. Ltd, 2024)
Background: Asthma, a prevalent and potentially debilitating chronic disease, is traditionally managed using reliever medications such as short-acting β2-agonists (SABA) or low-dose inhaled corticosteroids (ICS). Recent evidence, however, indicates that a combination of as-needed ICS and a rapid-acting long-acting β2-agonist (LABA) provides superior outcomes compared to SABA alone. Furthermore, this combination therapy is at least as effective as regular ICS in mitigating the risk of exacerbations. This emerging evidence highlights a significant shift in treatment strategies for mild asthma, underscoring the potential for enhanced management and improved patient outcomes with the new therapeutic approach. Methods: Following PRISMA 2020 guidelines, this systematic review focused exclusively on full-text articles published in English between 2014 and 2024. Result: The study conducted a comprehensive review of over 400 publications sourced from reputable databases, including ScienceDirect, SagePub, and PubMed. Folowing an initial screening, eight publications were identified as warranting more in-depth analysis. Conclusion: The study found that as-needed ICS/LABA is effective in preventing exacerbations in mild-to-moderate asthma patients, but less effective than regular ICS in improving FEV1 and ACQ scores. Combining ICS/LABA with SMART regimen was highest for severe exacerbations prevention.